Morphophysiological and anatomical responses of rice to water deficit stress after silicon seed priming - Rachmawati, Diah; Fadia Hayya, Nina; Maryani (Agriculture and Natural Resources, 2026)
Importance of the work: Silicon acts as a priming agent that enhances plant tolerance to water deficit stress. Objective: To analyze the interactive effect of sodium metasilicate concentrations and field capacity levels on the morphophysiological and anatomical responses of rice (Oryza sativa L. ‘Inpari 24 Gabusan’) under drought stress. Materials and Methods: A completely randomized design with three replications was applied using four silicon priming concentrations (0, 20, 40, 60 mM) and three field capacities (100%, 75%, 50%). Growth, pigment content, stress biomarkers and stomatal characters were analyzed at 42 d after transplanting. Results: Significant interaction effects were observed between silicon concentration and field capacity for all measured parameters. The combination of 60 Mm Na2SiO3 and 100% or 75% field capacity enhanced plant height, root length, chlorophyll content and membrane stability, while reducing malondialdehyde and proline accumulation. In contrast, under 50% field capacity, the benefits of silicon were reduced but remained superior to the untreated control. Stomatal density and aperture size peaked with 60 Mm Na2SiO3 at 100% field capacity, contributing to optimized water use and gas exchange. Main finding: Silicon priming at 60 Mm Na2SiO3 improved drought resistance in rice, primarily through a synergistic effect with higher soil moisture levels. The results from this study should provide valuable insights for developing rice varieties with improved drought resistance.